A Study On The Function Of Thermoplastic Starch As Matrics In Biocomposite - Hamzah, Mohammad Farid (Universiti Teknologi PETRONAS, 2016)
Starch-rice straw composite is a promising formulation for replacing petroleum based raw material when viewed from the environmental and cost perspective. A set of environmental friendly test samples derived from starch-rice straw composite will be prepared with different type of plasticizer which is Choline Chloride/Urea (Reline) and Choline Chloride/Glycerol (Glyceline) deep eutectic solvent with varying fibre loading of 10, 20 and 30 wt. %. The aim is to study the function of thermoplastic starch as matrices in biocomposite which is highly influenced by the type of plasticizer used. The change was observed via measurement the moisture absorption properties of the starch-rice straw composite of different plasticizer formulation. The moisture absorption percentage of the starch-rice straw composite was quantified in the form of weight differences between the initial dry weights of the composite with the weight of the test sample after the moisture absorption test.